Seismology of active regions: Current status and perspectives - Tripathy, Sushanta (Frontiers in Astronomy and Space Sciences, 2023)
The goal of helioseismology is to provide accurate information about the Sun’s interior from the observations of the wave field at its surface. In the last three decades, both global and local helioseismology studies have made significant advances and breakthroughs in solar physics. However, 3-d mapping of the structure and dynamics of sunspots and active regions below the surface has been a challenging task and is among the long standing and intriguing puzzles in solar physics due to the complexity of the turbulent and dynamic nature of magnetized regions. In this review, I present some of the recent results relevant for helioseismology of sunspots and active regions obtained from high resolution observations, forward modeling and numerical simulations.